Process Integration and Performance of Chilled Ammonia CO2 Capture Technology - Björk, Henric; Aronsson, Jesper (My University, 2011)
Global environmental concern with possible near-term political policies to increase cost for greenhouse gas emissions and an inclusion of aluminium production in the European emissions trading system have sparked an interest for CO2 capture within the aluminium industry. The aluminium manufacturing process produces large quantities of CO2 emissions through a noncombustion process, this limits the potential technologies for CO2 capture to post combustion only. A commercially available post combustion technology utilizes a solvent that is degraded in an oxidising environment, as is the case in aluminium manufacturing. The CO2 capture technology investigated in this study uses ammonia as solvent. Ammonia is not degraded by oxygen. The process integration of the chilled ammonia process CO2 capture technology in a novel aluminium manufacturing plant was investigated from a required reboiler duty and available heat from an integration point of view. The process gas leaving the aluminium manufacturing process is characterised by low CO2 concentration and high flow rates compared to applications such as coal-power plants and sour-gas removal from natural gas. The effects on performance and behaviour of the chilled ammonia process for these low CO2 concentrations have not been fully established and have therefore been investigated. The process integration was performed for a case with varying process gas flow rate and CO2 concentration. Gas properties were obtained from Hydro, the company operating the Sunndalsøra aluminium manufacturing plant studied in this report. To isolate and investigate the effects of varying CO2 concentration, a case with constant process gas flow rate was also studied. The CO2 concentration was varied between 4, 7, 10 and 15 vol%. To determine the amount of surplus heat available for process integration, a model of the process gas treatment train was created using the process simulation software Ebsilon Professional. The model consists of the existing process gas treatment train with the addition of two heat extractions for the top and bottom cycle process integration. The chilled ammonia process was described in two separate models in order to determine the required reboiler duties, one for CO2 capture in the bottom cycle and another for ammonia recovery in the top cycle. The simulation software Aspen Plus, handling heat and mass transfer, chemical reactions and complex solutions, was used for modelling. All components, except the top and bottom cycle absorbers, were modelled using an equilibrium calculation approach that assumes infinitely fast mass transfer and reaction kinetics in reactors. The absorbers were modelled using a rate-based approach in which also kinetics is considered, creating limiting factors for the speed and performance of the process. The CO2 capture rate was predetermined to 85% with a maximum ammonia slip of 10 ppmv. Through simulations it was observed that CO2 only has a moderate effect on the bottom cycle specific reboiler duty, in kJ/kg CO2 captured, but that the absolute reboiler duty increases as CO2 concentration and total CO2 content increases. The opposite effect was observed for the top cycle; with the absolute reboiler duty remaining relatively unchanged and the specific reboiler duty decreasing with increasing CO2 concentration. The reboiler temperatures were found to be 111°C for the top cycle and between 194-207°C for the bottom cycle. Through simulations of the process gas treatment train, it was established that surplus heat is available at temperatures sufficient for integration with the chilled ammonia process. It was found that the total heat demand for the chilled ammonia process could be covered to 50% by process integration for the best case scenario. The highest share of heat demand covered through process integration was achieved for the 4 vol% CO2 concentration case. The share then decreases with increasing CO2 concentration to 32% heat demand covered through integration for the 15 vol% case. The study concluded that increasing the CO2 concentration not necessarily will be economically favourable. The lower process gas flow rate associated with the higher CO2 concentration allows for the use of smaller process equipment, lowering investment costs. The lower share of heat demand covered through process integration will however increase operational costs meaning that the most economically feasible CO2 concentration is a trade-off between investment costs and operational costs.
Keywords: Energi; Kemisk energiteknik; Energy; Chemical energy engineering